2013
DOI: 10.1186/1471-2334-13-46
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic oral yeast carriage and antifungal susceptibility profile of HIV-infected patients in Kunming, Yunnan Province of China

Abstract: BackgroundOral Candida colonization and its relation with predisposing factors in HIV-infected patients have received wide concerns during recent decades. In this study, we investigated asymptomatic oral Candida carriage rate, species distribution and antifungal susceptibility of 604 HIV-infected patients and 851 healthy individuals in Kunming, Yunnan Province of China.MethodsMucosal swab sampling was taken from each subject and CHROMagar Candida agar medium and API 20C AUX system were used to identify yeast i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
53
1
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 27 publications
(52 reference statements)
12
53
1
9
Order By: Relevance
“…Most of the infections are related to Candida spp, which is generally a commensal in the oral cavity, but in immunologically-compromised patients it can assume pathogenic characteristics 2 . Some studies showed that candidiasis comes from commensal strains and that asymptomatic oral colonization can lead to oral lesions or become a source of disseminated infections 3-5 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the infections are related to Candida spp, which is generally a commensal in the oral cavity, but in immunologically-compromised patients it can assume pathogenic characteristics 2 . Some studies showed that candidiasis comes from commensal strains and that asymptomatic oral colonization can lead to oral lesions or become a source of disseminated infections 3-5 .…”
Section: Introductionmentioning
confidence: 99%
“…O aumento da incidência das infecções fúngicas tem sido associada a pacientes com comprometimento do sistema imunológico 1,2,3 , Candida albicans é a espécie frequentemente isolada 4,5,2,3 . No entanto, outras espécies têm aumentado significativamente sua prevalência, dentre estas C. tropicalis 6,3,7 .…”
Section: Introductionunclassified
“…No entanto, outras espécies têm aumentado significativamente sua prevalência, dentre estas C. tropicalis 6,3,7 . As infecções por C. tropicalis são comumente associadas a malignidade, com alguns estudos relatando sua alta incidência entre pacientes com doenças hematológicas, como por exemplo, leucemia mieloide aguda 8,9,10,11 , sendo causa comum de infecção em unidades de terapia intensiva, é um problema particular em pacientes neutropênicos 12,13, 14 .…”
Section: Introductionunclassified
“…The isolate was sensitive to all four tested antimycotics. In oral swabs from HIV-patients, Li et al (2013) found that one of the yeast isolates (frequency = 0.3% of isolates) was a Saccharomyces cerevisiae. The isolate was sensitive to all four tested antimycotics.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…Among these new papers, there were no relevant publications on the lack of toxicity or toxin production: in contrast production of peptaibols and the pyranone volatiles have been reported (Chen et al, 2013;Wickel et al, 2013). Most reports investigate the diversity of promising industrial use, which this species offers.…”
Section: Trichoderma Asperellummentioning
confidence: 99%